Avaliações metafísicas aristotélico-tomistas sobre o acesso à Justiça - Espindola, Diogo Malgueiro (2017)
This dissertation aims to undertake a metaphysic analysis about the constitutional right of the access to justice supported on the doctrines of Aristotle and St. Thomas of Aquin. The methodology used by the author was about bibliographic researchs and the analysis, the synthesis, and the critique applied to the actual stage of comprehension of the legal phenomenon from the perspective of the Philosophy of Law. From the contributions of Mauro Cappelleti and Bryant Garth, contained in their relatory about the access to justice, the author have found two different points of view and heading for the second: the production of just and effectiveness decisions to the people and to the society. The author’s research lead to the conceptions of Metaphysic and Physic in Aristotle’s Philosophy as the original source of this possibility exposed by Mr. Chiappin, as well as in Charitas doctrine in St. Thomas as possibility of universalization of the doctrine of the four causes that covers all the mankind, gathered under the label of natural law. The opening that this analysis provided, lead the author to a brand new level of understanding about the access to justice, which was examined under the aitiologic component of the aristotelic metaphysics. The conclusion was that the rehabilitation of the aristotelic-thomist way of think can magnify the men as the ground, the support and the end of the law through access to justice